Andhra Pradesh State Minorities Finance Corporation (APSMFC): A Survey of Beneficiaries - Shabbir, Ali (Indian Journal of Marketing, 2004)
The proportion of self-employed persons among minorities, especially Muslims, is quiet considerable. Their access to different sources of financial assistance is an important pre-requisite for enabling them to survive in the present day competitive business environment. With a view to facilitate this process the Government of Andhra Pradesh established Andhra Pradesh State Minorities Finance Corporation in 1985, to lend financial assistance to the needy among the minorities and to take up productive activities.